Rezolvati ecuatiile urmatoare ; .. b) 10 ( x-1) - 3 (4x-7) -2= 4(3x-5)+1 c) 3(2x-7)-5(x-2) -3=2(x-7)+7 d) 4(x-5)+3(3x-5)= 2(2x+5)-9 e) 5(2x+1) - 8 (1- x ) = 2 (3x+ 2)+5 f) 3 (5+4x) - 6 (x+2)=5(2x-1)- 4

1

Răspunsuri

2014-05-29T16:41:26+03:00
B)10(x-1) -3(4x-7)-2=4(3x-5)+1
10x-10 -12x+21-2=12x-19
-2x +9=12x -19
-14x=-28
=>-x=-2 =>x=2

c)3(2x-7)-5(x-2) -3=2(x-7)+7
6x-21-5x+10-3=2x-14+7
x-21+7=2x-14+7
x-21=2x-14
-21=x-14
x=-7


4(x-5)+3(3x-5)= 2(2x+5)-9
4x-20+9x-15=4x+10-9
13x-35=4x+1
13x-4=36
9x=36
x=4

5(2x+1) - 8  (1- x ) = 2 (3x+ 2)+5
10x+5-8+8x=6x+4+5
18x-3=6x+9
18x=6x+12
12x=12
x=1


3 (5+4x) - 6 (x+2)=5(2x-1)- 4
15+12x-6x-12=10x-5-4
3+6x=10x-9
12+6x=10x
12=4x
=>x=3


Asta a fost tot...sper ca te-am ajutat!